1920
DOI: 10.1001/archinte.1920.00090320077006
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Studies on the Respiration

Abstract: As the clinical value of determinations of the vital capacity of the lungs becomes more clearly emphasized \p=m-\ in heart disease, in tuberculosis, in aeronautics, etc.\p=m-\the problem of normal standards becomes increasingly important. For the clinician, the standard should require as few and simple measurements as are consistent with reasonable accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1921
1921
1950
1950

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Taken after patient had been receiving quinidin sulphate for two days (Feb 7,. Taken after patient had been receiving quinidin sulphate for two days (Feb 7,.…”
mentioning
confidence: 99%
“…Taken after patient had been receiving quinidin sulphate for two days (Feb 7,. Taken after patient had been receiving quinidin sulphate for two days (Feb 7,.…”
mentioning
confidence: 99%
“…The highest correlation coefficients are with total lung volume, vital capacity, and complemental air, in which they are of the order of 0 6 to 0 7 in males. The relationship between height and vital capacity was first recognized by Hutchinson (1846) and has since been confirmed by other workers (West, 1920;Cripps, Greenwood, and Newbold, 1923;Hurtado and Fray, 1933;Kaltreider, Fray, and Hyde, 1938;Aslett, d'Arcy Hart, and McMichael, 1939;Baldwin, Cournand, and Richards, 1948); it inevitably reflects itself in the complemental air and total lung volume.…”
Section: Resultsmentioning
confidence: 79%
“…These workers also calculated the correlation coefficients for vital capacity with height, height and weight, surface area (from du Bois' Tables) in a group of 400 male students aged 18 to 30 years. Lemon and Moersch (1924) compared the classifications and formula for determining the normal vital capacity proposed by Hutchinson (1846), Schuster (1911), Peabody and Wentworth (1917), Lundsgaard and van Slyke (1918), Dreyer (1919), West (1920), Hewlett andJackson (1922), andMyers (1923). They concluded that West's formula was the most exact and the easiest to use.…”
Section: Introductionmentioning
confidence: 99%